Investigating antibiotic use in Gaza Strip hospitals: A retrospective cross-sectional analysis - Alagha, Hala ZI; Al Telbani, Maha Jebreel (The Journal of Infection in Developing Countries, 2022)
Introduction: Rates of antimicrobial resistance in the Gaza Strip are rising while regulations on antibiotics use are weakly implemented. This study aimed to investigate antibiotic use in hospitals utilizing World Health Organization (WHO) hospital, prescribing, and patient care indicators. Methodology: A retrospective study was conducted at Al Shifa medical complex (SMC), Nasser Medical Complex (NMC), and European Gaza Hospital (EGH). Data for hospital indicators were collected from drug inventory records and by interviewing hospital pharmacy managers, while data for prescribing and patient care indicators were collected from medical records from all departments. WHO standard data collection forms and formulas to calculate quantitative indicators were used. Results: Standard treatment guidelines for infectious diseases were unavailable. The availability of key antibiotics on the day of the investigation was 58.62%, 90.9%, and 44.82%, and antibiotics were out of stock for 120.5, 63.3, and 119.8 days/year in SMC, NMC, and EGH, respectively. A total of 1400 patients’ records were screened; 68.2% of patients were prescribed antibiotics with an average duration of 3 days. The number of antibiotics prescribed was 1.26/hospitalization, 55% were prescribed by generic name, 98% were consistent with the essential medicine list, and 94.7% were given parenterally. Ceftriaxone was the most commonly used antibiotic (47.5%). Adherence rates to STGs for Caesarean section antibiotic prophylaxis and for pneumonia were 43% and 6.3%, respectively. About 97% of doses of prescribed antibiotics were administered and patients on antibiotics stayed in the hospital for 4.1 days. Conclusions: Antibiotic utilization patterns are less than optimal. Strategies to improve antibiotic use in the investigated hospitals are needed.